Measles and its Problems. A Clinical Analysis of Hospitalized Patients Under 5 Years of Age - Muzief Munir; I. Mustadjab; F. H. Wulur (Indonesian Pediatric Society, 1982)
Two hundred and sixty one cases of measles under 5 years of age admitted to the Pediatric Ward of Gunung Wenang Hospital Manado, lrulonesia, were analyzed.It is clearly evident tlwt measles in this country indeed, is one of the important child health problems, especially among those under 5 years of age. From this analysis it was found thoJ only 40 out of 261 cases or 15% suffered without any complications, but the remtJining 85% experienced complications.The younger the children suffering from measles, the more frequent would be the complications.The worse the nutritional status of the chNdren, the higher the rate of complications and mortality. In patients with a normal body weight, 52% were found not to have any complications. But the rate of complications increased in underweight and marasmic cases.Bronchopneumonia with or without gastroenteritis, was found more frequentlyin marasmic cases.The mortality rate was 13.8%- And it was highest among the marasmic cases, being 26%, while in normal body weight children it was only 6%.Measles encephalophathia was found in only 18 out of the 261 cases or 7% and mainly associated with bronchopneumonia and gastroenteritis.From this study, it is felt that further field studies should be carried out in this country in an attempt to determine the real magnitude of measles problems in the community.